Common learning and cooperation in repeated games - Takuo Sugaya; Yuichi Yamamoto (Theoretical Economics, 2020)
We study repeated games in which players learn the unknown state of the world by observing a sequence of noisy private signals. We find that for generic signal distributions, the folk theorem obtains using ex-post equilibria. In our equilibria, players commonly learn the state, that is, the state becomes asymptotic common knowledge.
Keywords: C72; C73; 330; Repeated game; private monitoring; incomplete information; ex-post equilibrium; individual learning